Lateral dorsal infundibular approach: an alternative option for the safe completion of difficult laparoscopic cholecystectomy - Juxian Song; Jian Chen; Shuguo Zheng (BMC Surgery, 2022)
Abstract Background Difficult laparoscopic cholecystectomy (LC) due to acute cholecystitis (AC) increases the risk of bile duct injuries and postoperative complications. Here, we added the lateral dorsal infundibular approach as an initial surgical maneuver during LC to improve outcomes. Methods We describe the detailed technical procedure of the lateral dorsal infundibular approach in patients with AC resulting in difficult LC. This technique was developed after nearly 10 years of experience in laparoscopic surgery, and has been routinely used in the past 5 years. We also retrospectively analyzed the perioperative data for 469 patients with difficult LC. Results A total of 469 patients with AC received difficult LC between July 2016 and June 2021, of which 438 (93.4%) performed a lateral dorsal infundibular approach. Sixty-four patients (13.6%) had variations of the hepatic bile duct and cystic duct according to preoperative magnetic resonance cholangiopancreatography, 438 patients (93.4%) received elective surgery, 31 (6.6%) received emergency surgery, and 10 (2.1%) underwent conversion. There was no postoperative bile leaks and no bile duct injuries in the described technique. Conclusion During difficult LC, the critical view of safety can be gradually achieved by changing the surgical approach to achieve cholecystectomy.